Socio Demographic Status of Victims in Vitriolage Cases- A Medico Legal Study (KYAMC Journal, 2017)
Vitriolage or acid violence is a burning human right violation problem of our country. Over the last few years, acid throwing in Bangladesh was a regular phenomenon where most of the victims were female. This descriptive cross sectional study was carried out from July 2011 to June 2012 among the victims of vitriolage who underwent treatment at One stop Crisis centre (OCC) and burn unit of Dhaka Medical College Hospital and also at the rehabilitation and treatment clinics of acid Survivors Foundation (ASF). Among the victims 92% were female and 25% belonged to 21-30 years age group. Most of the victims were from low socio economic background. Failure in marriage (22%), refusal of indecent proposal for sexual relationship (17%), failure in love affairs (13%) were the main causes behind acid violence. Fifty four percent (54%) had injuries in hand, 51 % (51) had injuries in neck and throat, 43 % (43) in back of body and 41 % (41) in face. The victims of vitriolage suffer in the form of physical, social, mental and economical ways. Rehabilitation centre for the victims, prevention of indiscriminate sale of acids, prompt trial of the accused, creation of acid crime tribunal in each district etc can improve the situation.KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 553-556